Mathematical Model Of Precious Securities Published On The Market (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Despite the fact that the stock market in Uzbekistan is not fully developed, the shares of many joint-stock companies are registered on the stock exchange and are being traded. Profits from stocks are realized in the form of dividends or in exchange for their secondary sale at a higher price. We use mathematical modules to decide which asset to invest in or not to invest in. We try to mathematically model some of these actions using linear stochastic differential equations (SDE) and the Euler-Maruyama scheme.